Antibacterial Activity of Cocoa Leaf Extract Theobroma cacao L. Against Acne-Causing Bacteria Cutibacterium Acnes and Staphylococcus epidermidis - Sartika Gunawan Putri; Sutriani Kaliu (Universitas Muhammadiyah Prof. Dr. Hamka, 2022)
Cocoa plantation waste (Theobroma cacao L.), cocoa leaves are increasingly abundant, with efforts to increase cocoa production by trimming the shape. The Ladongi sub-district in Kolaka Regency, Southeast Sulawesi, which produces the most cocoa beans, is also not spared from this. Cocoa leaves have not been used optimally, even though their phytochemical components have the potential as antibacterial. This study aims to determine the antibacterial activity of cocoa leaf extract (Theobroma cacao L.) against acne-causing Cutibacterium acnes and Staphylococcus epidermidis. The method used is the disc diffusion method (Kirby Bauer). The results showed that cocoa leaf extract had the potential as an antibacterial against acne-causing bacteria, Cutibacterium acnes, and Staphylococcus epidermidis with respectively the best inhibitory concentration of 25%, 19mm, and 22mm.